2017
DOI: 10.1002/hed.24744
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes with oral tongue squamous cell carcinoma in Finland

Abstract: The outcome of oral tongue SCC has significantly improved in Finland. However, the relatively high number of disease recurrences in patients with stage I and II disease, when compared with patients with stage III and IV disease, calls for an investigation of new treatment approaches. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1306-1312, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 28 publications
5
51
3
Order By: Relevance
“…In several studies, preference for males varied among 48% and 86.4% [18][19][20][21][22][23] and the male frequency we found (53.3%) is within the above-mentioned range. In the literature, mean age is widely variable, it was from 64.3 to 47.5 years, 18,[21][22][23][24] and in our study, it was slightly lower (63.9 years).…”
Section: Agesupporting
confidence: 82%
See 2 more Smart Citations
“…In several studies, preference for males varied among 48% and 86.4% [18][19][20][21][22][23] and the male frequency we found (53.3%) is within the above-mentioned range. In the literature, mean age is widely variable, it was from 64.3 to 47.5 years, 18,[21][22][23][24] and in our study, it was slightly lower (63.9 years).…”
Section: Agesupporting
confidence: 82%
“…An unexpected result was that in our study, the MDSCC was the most common of the analyzed tumors (56.7%), contrasting with previous data From Finland and India reporting that WDSCC was the most frequent SCCT. 20,23 50% of the analyzed patients were males with a mean age of 63.1 years and interestingly, 35.3% of the SCCs were in BT. BT located tumors were more frequent than previously published and as it was stated by Westra et al, 2 this finding could be related with the increase of HPV infection.…”
Section: Tnm Classificationmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies have reported that such cases had a high rate of lymph node metastasis, recurrence, and cancer-related mortality [2,3]. In our previous study covering all stages (I-IV) of OTSCC, stage II Table 1 T staging criteria for small OTSCC (≤ 4 cm in diameter) with clinically negative neck in the AJCC 7th, the AJCC 8th (which incorporated depth of invasion, DOI (DOI is the measurement of depth of invasion and not tumor thickness)), and our proposal using a lower cutoff point for DOI patients had a poor survival, which was almost similar to stage III patients [14]. This indicates understaging in some stage II cases according to the AJCC 7th [5].…”
Section: Discussionmentioning
confidence: 67%
“…Oral tongue squamous cell carcinoma (OTSCC) is globally the most frequent type of oral cancer in terms of epidemiology [1]. It is a highly aggressive cancer associated with a low rate of local tumour control, and, despite advances in diagnostics and therapeutics, the 5-year survival rate remains low, around 60% [2].…”
Section: Introductionmentioning
confidence: 99%